LAND LAW ENFORCEMENT IN VILLAGES BASED ON MEDIATION: EFFORTS TO ACHIEVE SUBSTANTIVE JUSTICE IN THE COMMUNITY - Darmanik, Pandapotan; Hulu, Fonaha; Damanik, Yuni Tresia Sastika (Faculty of Law, Universitas Pekalongan, 2024)
Land law enforcement at the village level in Indonesia faces complex challenges, including the dualism of legal systems and limited public access to land information. The mediation approach in resolving land disputes in villages offers solutions that align with local values and are supported by various laws and regulations, but its implementation still faces challenges that require a comprehensive and contextual approach. The aim of this research is to analyze the implementation of mediation-based land law enforcement at the village level in an effort to achieve substantive justice for the community, as well as to identify factors that influence the effectiveness of mediation in resolving land disputes in villages. This research uses a normative legal research method with a statutory and conceptual approach, focusing on the study of legal norms, legal principles, and legal concepts related to mediation-based land law enforcement at the village level. Data collection techniques are carried out through literature study, while data analysis uses qualitative analysis methods with deductive reasoning, involving data organization, categorization, interpretation, and drawing conclusions. The research results show that the implementation of mediation-based land law enforcement at the village level to achieve substantive justice is a complex approach involving several main stages, from dispute identification to agreement monitoring. This approach combines formal legal principles with local wisdom, paying attention to key aspects such as respect for local values, equality, and transparency. Its effectiveness is influenced by various interrelated factors, including the legal framework, mediator capacity, participation of disputing parties, understanding of local context, resource support, inter-agency coordination, and political support. Despite facing challenges, proper implementation has the potential to effectively resolve land disputes and contribute to strengthening village governance and sustainable rural development.